Integrated approach to the in vivo genotoxic effects of a titanium dioxide nanomaterial using LacZ plasmid-based transgenic mice - Louro, Henriqueta (2015)
Titanium dioxide (TiO2 ) nanomaterials (NMs) are widely used in a diversity of products including cosmetics, pharmaceuticals, food, and inks, despite uncertainties surrounding the potential health risks that they pose to humans and the environment. Previous studies on the genotoxicity of TiO2 have reported discrepant or inconclusive findings in both in vitro and in vivo systems. This study explores the in vivo genotoxic potential of a well-characterized uncoated TiO2 NM with an average diameter of 22 nm (NM-102, from JRC repository) using several genotoxicity endpoints in the LacZ plasmid-based transgenic mouse model. Mice were exposed by intravenous injection to two daily doses of NM-102: 10 and 15 mg/kg of body weight/day. Micronuclei were analyzed in peripheral blood reticulocytes 42 hr after the last treatment. DNA strand breaks (comet assay) and gene mutations were determined in the spleens and livers of the same animals 28 days after the last treatment. Histopathological and cytological analyses were also performed in liver samples. Genotoxic effects were not detected in mice exposed to the nanosized TiO2 under the experimental conditions used, despite a moderate inflammatory response that was observed in the liver. Considering the biopersistence of TiO2 in mouse liver and the moderate inflammatory response, the possibility of a secondary genotoxic effect at higher doses and in conditions that result in a stronger inflammatory response, for example, within a longer time window, should be investigated further.